2005
DOI: 10.2202/1475-3693.1046
|View full text |Cite
|
Sign up to set email alerts
|

The Sources of Inflation in Egypt: A Multivariate Co-integration Analysis

Abstract: The aim of this paper is to empirically investigate the sources of inflation in Egypt. For this, price dynamics is herein represented by a vector error-correction model, which we use to test for the existence of a long-run relationship between the consumer price index, real gross domestic product (GDP), the exchange rate, interest rate, money supply and world prices. Then using the augmented VAR approach, we test for Granger non-causality between the different variables and inflation. The main results that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The low R 2 s in all the output gap models is indicative that much of the variations remain to be explained. This finding is consistent with the literature in that real factors such as output gaps have no explanatory power in determining inflation in emerging markets (Loungani and Swagel, 2001;El-Sakka and Ghali, 2005;Ramakrishnan and Vamvakidis, 2002 ).…”
Section: Out-of-sample Forecastssupporting
confidence: 92%
“…The low R 2 s in all the output gap models is indicative that much of the variations remain to be explained. This finding is consistent with the literature in that real factors such as output gaps have no explanatory power in determining inflation in emerging markets (Loungani and Swagel, 2001;El-Sakka and Ghali, 2005;Ramakrishnan and Vamvakidis, 2002 ).…”
Section: Out-of-sample Forecastssupporting
confidence: 92%
“…Darrat (1997), Deme and Fayissa (1995) and Boujelbene and Boujelbene (2010) find that import prices are an important determinant for the level of inflation. Several studies Boschi and Girardi (2007), Darrat (1997), El-Sakka and Ghali (2005) and Boujelbene and Boujelbene (2010) have also taken into account of countries exchange rates when explaining the level of inflation. Furthermore, Kandil (2005) and Kose et al (2012) show that the cost of borrowing capital (interest rates) is an important determinant for inflation especially on the cost-push side.…”
Section: Empirical Modelmentioning
confidence: 99%
“…One policy measure is establishing a nominal anchor for the monetary policy to stabilize inflation expectation and hence lower inflation rates. In addition, previous studies showed that structural reforms based on improving Egypt's productive capacity, reducing the budget deficit and national debts, are crucial for controlling inflation (El-Sakka and Ghali, 2005 [35]). Keskek and Orhan (2010) [16] found strong evidence, using data from Turkey, that inflation-oriented monetary policy effectively reduces the inflation persistence and eliminates uncertainty.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%